Implementing green campus in UiTM Perak: was it challenging? Were there solutions? / Haryati Mohd Isa ... [et al.] - Mohd Isa, Haryati; Sedhu, Daljeet Singh; Azhar, Nurhusniah; Mohd Nor, Othman; Iffahd, Mohd (2021)
Green initiatives have become a global phenomenon now. This has been taken seriously by all parties with regard to the process of environmental sustainability. Sustainable Development Goals has been used as a guideline towards this agenda. The Malaysian government had issued the Green Technology Policy in July 2009 to accelerate the national economy and promote sustainable development. Furthermore, green technology has been applied to universities in Malaysia through several green initiatives to achieve green campus status under the UI Green Metric. There are several universities in Malaysia which have begun to seriously tackle the issue of green campus including UiTM Perak. Two research objectives had been developed: (1) to identify challenges in implementing a green campus in UiTM Perak and (2) to recommend solutions to overcome the challenges in implementing green campus in UiTM Perak. A qualitative method approach by using a semi-structured interview had been adopted. The Green campus committee in UiTM Perak were interviewed. The data obtained were analysed using content analysis. The research revealed that despite several green initiatives being implemented by UiTM Perak, there are also certain challenges to be overcome. These challenges include financial constraints, lack of awareness and knowledge. In order to overcome these challenges, the management of UiTM Perak had outlined the necessary steps to be taken. In conclusion, green campus initiatives can provide many benefits towards a sustainable environment in UiTM Perak. However, this agenda requires the concerted effort of all parties involved.